2013
DOI: 10.1152/ajpendo.00460.2012
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between calcium and phosphorus in the regulation of the production of fibroblast growth factor 23 in vivo

Abstract: Quinn SJ, Thomsen AR, Pang JL, Kantham L, Bräuner-Osborne H, Pollak M, Goltzman D, Brown EM. Interactions between calcium and phosphorus in the regulation of the production of fibroblast growth factor 23 in vivo. Am J Physiol Endocrinol Metab 304: E310 -E320, 2013. First published December 11, 2012; doi:10.1152/ajpendo.00460.2012.-Calcium and phosphorus homeostasis are highly interrelated and share common regulatory hormones, including FGF23. However, little is known about calcium's role in the regulation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
80
0
2

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(91 citation statements)
references
References 48 publications
9
80
0
2
Order By: Relevance
“…These data, support recent experimental evidence pointing to interactions between calcium and phosphorus in the regulation of FGF-23 production (50,51). Because increases of FGF-23 in renal transplant patients have been correlated with both poor graft function and patient survival (52), it is reassuring that levels remained low.…”
Section: Evenepoel Et Alsupporting
confidence: 83%
“…These data, support recent experimental evidence pointing to interactions between calcium and phosphorus in the regulation of FGF-23 production (50,51). Because increases of FGF-23 in renal transplant patients have been correlated with both poor graft function and patient survival (52), it is reassuring that levels remained low.…”
Section: Evenepoel Et Alsupporting
confidence: 83%
“…Ca and P have been shown to independently and synergistically stimulate FGF-23 (26). Thus, therapies for SHPT may indirectly affect FGF-23 production mediated by their effects on Ca and P metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…There are also data to suggest that calcium may participate in a synergistic fashion with phosphate to regulate FGF23 levels [42]. In a particularly informative study that involved the PTH knockout mouse, the calcium-sensing receptor knockout mouse and/or the double knockout mouse, Quinn et al showed that the greatest changes in serum FGF23 were accounted for by changes in the calcium x phosphate product, suggesting that both calcium and phosphorus may act in a synergistic fashion to regulate FGF23 levels.…”
Section: Pth and Fgf23mentioning
confidence: 99%